If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) * 3x = 37 Reorder the terms: 2(1 + x) * 3x = 37 Reorder the terms for easier multiplication: 2 * 3x(1 + x) = 37 Multiply 2 * 3 6x(1 + x) = 37 (1 * 6x + x * 6x) = 37 (6x + 6x2) = 37 Solving 6x + 6x2 = 37 Solving for variable 'x'. Reorder the terms: -37 + 6x + 6x2 = 37 + -37 Combine like terms: 37 + -37 = 0 -37 + 6x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -6.166666667 + x + x2 = 0 Move the constant term to the right: Add '6.166666667' to each side of the equation. -6.166666667 + x + 6.166666667 + x2 = 0 + 6.166666667 Reorder the terms: -6.166666667 + 6.166666667 + x + x2 = 0 + 6.166666667 Combine like terms: -6.166666667 + 6.166666667 = 0.000000000 0.000000000 + x + x2 = 0 + 6.166666667 x + x2 = 0 + 6.166666667 Combine like terms: 0 + 6.166666667 = 6.166666667 x + x2 = 6.166666667 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. + 0.25 + x2 = 6.166666667 + 0.25 Combine like terms: + 0.25 = 1.25 1.25 + x2 = 6.166666667 + 0.25 Combine like terms: 6.166666667 + 0.25 = 6.416666667 1.25 + x2 = 6.416666667 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 6.416666667 Calculate the square root of the right side: 2.533114026 Break this problem into two subproblems by setting (x + 0.5) equal to 2.533114026 and -2.533114026.Subproblem 1
x + 0.5 = 2.533114026 Simplifying x + 0.5 = 2.533114026 Reorder the terms: 0.5 + x = 2.533114026 Solving 0.5 + x = 2.533114026 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 2.533114026 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 2.533114026 + -0.5 x = 2.533114026 + -0.5 Combine like terms: 2.533114026 + -0.5 = 2.033114026 x = 2.033114026 Simplifying x = 2.033114026Subproblem 2
x + 0.5 = -2.533114026 Simplifying x + 0.5 = -2.533114026 Reorder the terms: 0.5 + x = -2.533114026 Solving 0.5 + x = -2.533114026 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -2.533114026 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -2.533114026 + -0.5 x = -2.533114026 + -0.5 Combine like terms: -2.533114026 + -0.5 = -3.033114026 x = -3.033114026 Simplifying x = -3.033114026Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.033114026, -3.033114026}
| 2x-5=36 | | p^3+2p^2-4p-8=0 | | 9x-7=4x-7+5x | | m/-6=8 | | 4f+7=9 | | (3x+2)2+(4x-3)2=(5x-1)2 | | 6x^3+x^2+x=0 | | 6x^2+19x+7=-1 | | r-5.4=9.2 | | 9-n/3=28 | | 3x-5=4x+9 | | 100x^4+399x^2-4=0 | | 3(x+6)=3x+18 | | 11=2g-5 | | 876-4x=14x+19 | | 5-9x=190-44x | | -6w+18=20w | | 7=t-6-3 | | 3(m-3)+7(m+3)=16-4(7-m) | | 2x+3=4(x-1)+3 | | X^2-12x+36(x-6)=27(x-8) | | X+1+x=2+2x-1 | | 6k-3=-15 | | 7(x-4)-3=46 | | 2/5(25z-30)=3/5(12z+16) | | 12-8x=137-43x | | 81xy^3+3x^4=0 | | 122-3x=15x+20 | | 4(2x-8)-2=4(x-4)+6 | | 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 |